SUCCOR cone study: conization before radical hysterectomy. Issue 2 (17th January 2022) - Chacon, Enrique; Manzour, Nabil; Zanagnolo, Vanna; Querleu, Denis; Núñez-Córdoba, Jorge M; Martin-Calvo, Nerea; Căpîlna, Mihai Emil; Fagotti, Anna; Kucukmetin, Ali; Mom, Constantijne; Chakalova,, Galina; Shamistan, Aliyev; et al.
Abstract : Objective: To evaluate disease-free survival of cervical conization prior to radical hysterectomy in patients with stage IB1 cervical cancer (International Federation of Gynecology and Obstetrics (FIGO) 2009). Methods: A multicenter retrospective observational cohort study was conducted including patients from the Surgery in Cervical Cancer Comparing Different Surgical Aproaches in Stage IB1 Cervical Cancer (SUCCOR) database with FIGO 2009 IB1 cervical carcinoma treated with radical hysterectomy between January 1, 2013, and December 31, 2014. We used propensity score matching to minimize the potential allocation biases arising from the retrospective design. Patients who underwent conization but were similar for other measured characteristics were matched 1:1 to patients from the non-cone group using a caliper width ≤0.2 standard deviations of the logit odds of the estimated propensity score. Results: We obtained a weighted cohort of 374 patients (187 patients with prior conization and 187 non-conization patients). We found a 65% reduction in the risk of relapse for patients who had cervical conization prior to radical hysterectomy (hazard ratio (HR) 0.35, 95% confidence interval (CI) 0.16 to 0.75, p=0.007) and a 75% reduction in the risk of death for the same sample (HR 0.25, 95% CI 0.07 to 0.90, p=0.033). In addition, patients who underwent minimally invasive surgery without prior conization had a 5.63 times higher chance of relapse compared with those who had an open approach and previous conization (HR 5.63, 95% CI 1.64 to 19.3, p=0.006). Patients who underwent minimally invasive surgery with prior conization and those who underwent open surgery without prior conization showed no differences in relapse rates compared with those who underwent open surgery with prior cone biopsy (reference) (HR 1.94, 95% CI 0.49 to 7.76, p=0.349 and HR 2.94, 95% CI 0.80 to 10.86, p=0.106 respectively). Conclusions: In this retrospective study, patients undergoing cervical conization before radical hysterectomy had a significantly lower risk of relapse and death.